Adoption of online social media innovation: Who's inside the spectrum? - Raziuddin, Khan Md Raziuddin; Shahriar, Faisal Mohammad (© 2014, IGI Global., 2018)
This book chapter was published in the book named Digital Arts and Entertainment: Concepts, Methodologies, Tools, and Applications [© 2014, IGI Global.] and the definite version is available at: http://doi.org/10.4018/978-1-4666-6114-1.ch025 The Article's website is at: https://www.igi-global.com/gateway/article/75459#pnlRecommendationForm